Severe acute hepatitis by coinfection by epstein-barr viruses and citomegalovirus - case report and review of literature: Hepatitis Aguda Grave por Coinfeccion por Virus Epstein-barr y Citomegalovirus- reporte de caso y revisión de la literatura - Valero Román, Ítalo Renato (2019)
We report the case of a 6-year-old patient with a history of atopic dermatitis. Some days before her hospitalization she presented rhinorrhea and cough. Subsequently she presented maculopapular lesions, increase of body temperature and yellowing of the skin. After being hospitalized, in addition to the symptoms described, she presented 2 episodes of spontaneous epistaxis, hematemesis and melena; while in the physical examination, mucocutaneous jaundice, fever, generalized maculopapular rash, lymphadenopathy, and hepatosplenomegaly were evident. In the images studies, signs that indirectly indicated acute hepatitis and pleural effusion, were found. On the other hand, among the serological results, it was found that the markers of acute infection by EBV and CMV, as well as the marker of chronic EBV infection, were positive. As far as we know, this is the first report of CMV-EBV coinfection in our, due to an acute CMV infection. We report the case and we carry out a review of the literature.